Landslide Hazards and Risks in Tanon, Sragen, Central Java Province - Suwarno, Suwarno (Forum Geografi, 2004)
The aims of this research are 1) to study and classify the landslide hazard of the study area, and 2) to evaluate the landslide risk of the research area. Field survey and laboratory analysis were used in this research. Terrain characteristic and social economic data were collected by purposive sampling. The structure of terrain unit based on landform unit map, slope map, soil map, and landuse map. Terrain parameters were divided into five classes; that were no hazard, low hazard, medium hazard, high hazard, and highest hazard classes. The risk classes were divided into four classes, that were no risk, low risk, midium risk, and high risk. Based on the landform units, soil type and the land used, the study area can be divided into 27 terrain units. The terrain units are differentiated into the landslide hazard classes and their landslide risk. In the study area there were found 5 classes of landslide hazard, namely 1) no hazard (2 terrain units); 2) low hazard (4 terrain units); 3) medium hazard (8 terrain units); 4) high hazard (11 terrain units); and 5) highest hazard (2 terrain units). Most of the high hazard class are located on hilly terrain units. Distribution of landslide risk in the study area are as follow: 4 terrain units have no risk; 17 terrain units have low risk; 4 terrain units in medium risk; and 2 terrain units have high risk. High risk are mostly located on hilly area with closely populated area.